2011
DOI: 10.1177/001946461004800101
|View full text |Cite
|
Sign up to set email alerts
|

Associational culture and civic engagement in colonial Lucknow

Abstract: Despite their importance in forging notions of civility, civic engagement and political participation, nineteenth century voluntary associations have received little attention in the growing body of literature on the rise and nature of civil society in India. This article explores the mutually constitutive relationship between voluntary association and middle-class formation through the example of the Jalsah-e Tahzib (est. 1868), the first voluntary society in colonial Lucknow. A cross-communal alliance of Hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…While the following section of this article on the Club's contemporary spatial setting and the section on 'State-led public, informalization of the state, goonda raj' rest on long-term ethnographic work in the neighborhood, the two historical sections complement this with Ulrike Stark's historiography (Stark 2011) and Congress records from between 1900 and 1940, respectively. As a red thread, the oral history of the Club's then caretaker Pandey-Ji weaves all four sections of the article together, building on almost weekly, often hour-long conversations with him throughout 2012.…”
Section: Methodsmentioning
confidence: 99%
“…While the following section of this article on the Club's contemporary spatial setting and the section on 'State-led public, informalization of the state, goonda raj' rest on long-term ethnographic work in the neighborhood, the two historical sections complement this with Ulrike Stark's historiography (Stark 2011) and Congress records from between 1900 and 1940, respectively. As a red thread, the oral history of the Club's then caretaker Pandey-Ji weaves all four sections of the article together, building on almost weekly, often hour-long conversations with him throughout 2012.…”
Section: Methodsmentioning
confidence: 99%
“…20Stark, “Associational Culture and Civic Engagement.” Urdu publicists and intellectuals associated with the Jalsah-e Tahzib , as Stark explores, began to translate “public good” as rifah-I ‘am .…”
Section: Notesmentioning
confidence: 99%
“…As Farina Mir has suggested of the Punjabi Hir-Ranjha epic that moved across multiple genres and registers over the centuries, 18 I will argue that stories of Mughal rulers circulating through the Indian-language press provided a sociocultural meeting place, but also a shared political language that linked older "templates of justice" 19 with nineteenthcentury understandings of the public good. 20 The nineteenth-century Indian print world that Bhatt entered in the 1870s was a site of experimentation with new genres and new ways of integrating news and entertainment, both to sell copy and to shape public opinion. Indian papers were, like many early newspapers worldwide, highly diverse containers.…”
Section: Introduction: Indian News As An Imperial Crisismentioning
confidence: 99%
“…Their appropriation of an Anglicised vocabulary of aspirations such as 'improvement', 'progress' and 'public good' comprised, as memorably put by Douglas Haynes, a 'conceptual straitjacket' by which these organisations further embedded colonial hegemony in India's associational life (Haynes 1991: 145-6, Chatterjee 1986. While this framework has been heavily applied in studies of colonial India's urban public sphere, it has been both implicitly and explicitly critiqued by a number of excellent recent studies of colonial Lucknow (Joshi 2001, Stark 2011, Perkins 2013). Many of these have shown that the array of public associations that emerged in Lucknow did not, like some larger 'All India' organisations, simply appear to emulate colonial deliberative models, but instead often seemed to ground themselves in motifs and symbols drawn from the city's mythologised history.…”
mentioning
confidence: 99%
“…The earliest significant organisation of this kind was the Anjuman-i-Hind-i-Awadh, a landlord-based group set up in 1861 to petition the government on the loyal ta'luqdari (landholding) interest, which ultimately set a prototype for the emergence of a wider inventory of middle-class and professional associations. The Jalsa-i-Tehzib, founded in 1868 by a number of Hindu and Muslim government officials and journalists, was more deeply rooted among the city's urban literati; it sought to provide a new forum for discussing issues of public significance (Stark 2011). By the 1890s, the more openly political Rifah-i-'Am was active in pressing a particular vision of the 'common good' as was embedded in its own title, making representations before the colonial bureaucracy on this basis.…”
mentioning
confidence: 99%